ANALISIS PENERAPAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM PEMBIASAAN KARAKTER DI SD MUHAMMADIYAH INOVATIF MERTOYUDAN - Wardana, Aditia Eska; Rahmawati, Puji (Universitas Muria Kudus, 2024)
The aim of this research is to analyze the implementation of the project to strengthen the profile of Pancasila students in character training.The research method used is descriptive qualitative. The research was carried out from March to June 2023. The data collection techniques used were interviews and documentation. The informants in the research were the principal and class I and IV teachers at Mertoyudan Innovative Elementary School. Data sources were obtained from informant information and documentation data. The informant selection technique uses purposive sampling. The data validity technique uses triangulation of source data and data. Data analysis uses a qualitative data analysis model.The results of the research state that there are 5 steps in planning the Pancasila student profile project, namely: forming a project facilitator team for strengthening the Pancasila student profile, identifying the level of readiness of the educational unit, designing dimensions, themes and time allocation for the project strengthening the Pancasila student profile, Developing project modules, designing a strategy for reporting project results. The implementation of the learning project to strengthen the profile of Pancasila students is in order to shape children's personalities in accordance with the profile of Pancasila students. In the learning implementation stage, the project for strengthening the profile of Pancasila students is not much different from intracurricular learning activities, however, the learning project for strengthening the profile of Pancasila students is packaged more lightly and fun. Some of the activities carried out are preparing learning resources or tools and materials, dividing groups, introduction stage, action stage and reflection or sharing stage. P5 activities carried out include; Make a VASE from paper mache, make a doormat, make a pencil case from used materials.